PENYALAHGUNAAN ASET PEMERINTAH DAERAH OLEH PEDAGANG PUSAT KULINER KELAPA GADING KELURAHAN SUNGAI BERINGIN KABUPATEN INDRAGIRI HILIR TAHUN 2021-2022 - Nanda, Alfrezi; ', Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This article discusses the misuse of Regional Government assets. Assets in general are things or anything that has economic value. There is misuse of assets belonging to the Regional Government of Indragiri Hilir Regency, namely the Kelapa Gading Culinary Center. The cause of misuse is the Kelapa Gading Culinary Center belonging to the Regional Government of Indragiri Hilir Regency. This is an indication that immigrants from the food court market are committing violations. The purpose of this research is to determine the causes of asset misuse and to determine the security and maintenance process of the Kelapa Gading Culinary Center. This research theory uses the Fraud Triangle Theory, namely Pressure, Opportunity and Rationalization. The research method used is a qualitative method by explaining descriptive data. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. The cause of the abuse occurred due to the weakening of security and maintenance of the Kelapa Gading Culinary Center by the Regional Government. This abuse was not carried out by the original traders of the Kelapa Gading Culinary Center, but was misused by migrants from the Tembilahan City Food Court Market which previously burned down. Weak security and maintenance by the Regional Government means that the Regional Government does not expect a decrease in the number of visitors. Keywords: Misuse, Assets, Security, Maintenance